Sarcastic Utterances in Majelis Lucu Indonesia Podcast: Pragmatics Analysis - Aprillia, Dinda; Damanik, Sisila Fitriany (LINGUISTIK TERAPAN, 2024)
This study aims to identify four types of sarcasm in each utterance spoken by the speakers on the YouTube Channel "Majelis Lucu Indonesia" (MLI) on the podcast video "Naik Jin ke Amerika Cuma 2 Jam"- episode 44. The object of this research is the conversation between 2 persons taken from a podcast video on the YouTube Channel. The results of this study show that in the podcast there are several speakers' utterances that contain the four types of sarcasm, among the four types of sarcasm-proportional sarcasm, lexical sarcasm, like-prefixed sarcasm, and illocutionary sarcasm, from speakers in the podcast video. The total number of speakers’ utterances in the podcast is fifty-eight (58) which is divided into four types of sarcasm. As the result, there are 21 proportional sarcasm utterances, 23 lexical sarcasm utterances, 9 like-prefixed Sarcasm utterances, and 5 illocutionary sarcasm in the podcast video. This provides useful information to find out the utterances of the four types of sarcasm and what type of utterance they belong to be associated with the sarcasm utterances in the podcast video.